O impacto da distribuição de ninhos de formiga e de efeitos associativos em interações formiga-planta mediadas por nectários extraflorais - Moura, Renan Fernandes (2021)
Ecological interactions are widely distributed in nature and can affect the diversification and maintenance of the global biodiversity. In this dissertation, we evaluated how several ecological variables affect the intensity of mutualistic interactions between ants and plants with extrafloral nectaries (EFNs), how such interactions affect and are affected by associative interactions between Cerrado plants, and, at last, we performed a comprehensive review aiming to quantify the impact of associative effects among plants in a broader sense. In the first chapter, we evaluated the effects of ant nest distribution and richness, in addition to the potential effects caused by the presence of neighboring plant species with EFNs, on a liana plant from the Brazilian Cerrado, Smilax Polyantha. We sampled ant nests and neighboring plants with EFNs around each S. polyantha, and measured its foliar herbivory and fruit production. We observed that higher densities of ant nests contributed to a reduction of foliar herbivory and to increases in fruit production. However, higher ant nest richness was associated with higher foliar herbivory values, while the diversity of neighboring plants was associated with reductions in herbivory and fruit production. The effects of ant nest distribution were, thus, antagonistic. In the second chapter, we tested the associative effects between S. polyantha and support plants on the herbivory and fruit production of S. polyantha. We measured foliar herbivory, fluctuating asymmetry, and the fruit production of S. polyantha, and we verified the presence of EFNs in support plant species. Smilax polyantha individuals associated with plants with EFNs were more visited by ants and had lower herbivory and fluctuating asymmetry. Plants with EFNs can, thus, benefit closely distributed plants and possibly impact the structuring of plant communities. In the third chapter, we performed an extensive quali-quantitative review about associative resistance (AR) between plants. We initially performed a historical review regarding the AR term, and then we conducted a quantitative review. We gathered data from studies on online databases and used meta-analytical tools to identify and measure the main mechanisms behind AR and measure them against a series of ecological variables (e.g., plant traits, and spatial variables). At last, we discuss the patterns found and their implications for biological control practices and the structuring of communities. We conclude that the intensity and direction of ecological interactions rely not only on the directly involved species, but on the surrounding ecological context. In the current global scenario, preserving plant biodiversity is essential since it is associated with the maintenance of biodiversity as a whole.